Research methods for sports studies - Gratton, C.; Jones, I. (Routledge, 2010)
This comprehensive, accessible and practical textbook provides a complete grounding in both qualitative and quantitative research methods for the sports studies student. The book offers the reader a step-by-step guide to the research process, from designing a research project, to collecting and analyzing data, to reporting the research, and is richly illustrated throughout with sport-related case-studies and examples from around the world. Now in a fully revised and updated new edition, the book covers key topics such as: